Early Modern Britain's Relationship to Its Past : The Historiographical Fortunes of the Legends of Brute, Albina, and Scota - Robinson-Self, Phil, 1979- (Book collections on Project MUSE., 2018)
"This volume considers the reception in the early modern period of three popular medieval myths of nationhood--the legends of Brutus, Albina, and Scota--tracing their intertwined literary and historiographical afterlives. The book is particularly timely in its dialogue with current investigations into early modern historiography and the period's relationship to its past, its engagement with pressing issues in identity and gender studies, and its analysis of British national origin stories at a time when modern Britain is considering its own future as a nation"--